Arbitration in smart contracts disputes: A look into the future - Jovanović Stefan (Anali Pravnog Fakulteta u Beogradu)
The paper explores the growing integration of blockchain technology in the legal field, specifically focusing on the emergence of smart contracts with their automated execution of contractual obligations. Technology experts believe that the use of smart contracts contributes to the eradication of disputes. However, the author challenges this claim while analyzing the disputes that may arise in this area, including classic contract law disputes and new issues specific to smart contracts. The paper focuses on whether arbitration is the optimal forum for resolving these disputes. The relationship between traditional and blockchain arbitration is explored, examining disputes that would be resolved using established methods and those suitable for the newly created mechanism. The interests of traditional arbitration do not coincide with those of blockchain arbitration. Both should cooperate and take advantage of each other. The author asserts that the flexibility and adaptability of arbitration will be its dominant advantage in addressing these disputes.